Rosie the twilight dragon - Mara, Maddy; Szepesi Szucs, Barbara (New York, NY : Scholastic Inc., 2022)
Rosie, Phoebe, and Stella all share an incredible secret: When they travel to a place called the Magic Forest, they can transform into powerful creatures called Night Dragons. Once there, the friends must save the Magic Forest from an evil that threatens to banish nighttime--forever. Rosie is determined to help! Her first task is to save the forest's magical daydreams from being destroyed by pesky Fire Sparks. Without the Night Dragons, the Magic Forest's hopes for survival will go up in smoke!
4.8
3-6
Keywords: Dragons -- Juvenile fiction; Magic -- Juvenile fiction; Friendship -- Juvenile fiction; Dragons -- Fiction; Magic -- Fiction; Friendship -- Fiction; Fantasy; Fantasy fiction